The Effect of Additioning Microencapsulated Noni Fruit Extract (Morinda Citrifolia Linn.) Product as A Feed Additive on Sentul Layer Phase Chickens Performance - KRISHADI, MUTIARA DWINA; Widjastuti, Tuti; Tanwiriah, Wiwin (Fakultas Peternakan, Universitas Padjadjaran, 2024)
This study aimed to find out what happened to the performance of Sentul chickens when microencapsulated noni fruit (Morinda citrifolia Linn.) extract was added to their food during the production phase. The research employed a sample of 40 Sentul hens aged 24 weeks and spanned 12 weeks. The investigation used a completely randomized design (CRD) and an experimental method. The treatments comprised five distinct types: P0 (basal diet), P1 (basal diet supplemented with 50 mg/kg zinc bacitracin), P2 (basal diet supplemented with 75 mg/kg MEBM), P3 (basal diet supplemented with 150 mg/kg MEBM), and P4 (basal diet supplemented with 225 mg/kg MEBM). The study's findings indicate that the P4 treatment statistically impacted the mean egg weight. Similarly, the P3 treatment also significantly influenced hen day production and feed conversion ratio (FCR layer) but did not appear to affect feed consumption. Ultimately, adding microencapsulated noni fruit extract to the diet at 150 mg/kg MEBM and 225 mg/kg MEBM concentrations can raise the average egg weight, the number of days that hens lay eggs, and the feed conversion ratio.